Consistent Condom and Lubricant Use and Associated Factors Amongst Men Who Have Sex with Men in Sub-Saharan Africa: A Systematic Review - Ratif Abdulai; Edith Phalane; Kyeremeh Atuahene; Refilwe Nancy Phaswana-Mafuya (Sexes)
Men who have sex with men (MSM) in sub-Saharan Africa (SSA) are disproportionately affected by the human immunodeficiency virus (HIV) compared to adult men in the general population. Unprotected anal sexual intercourse is a high-risk behavior for HIV infection. This makes the correct and consistent use of condoms with condom-compatible lubricants crucial in reducing further HIV acquisition amongst the MSM population in SSA. However, consolidated data on the scope of the consistency of condom use with lubricants among MSM in SSA is lacking. In this regard, it was necessary to consolidate existing evidence on consistent condom usage with lubricants, as well as associated context-specific factors among the MSM population in SSA. A systematic review was conceptualized and registered with the International Prospective Register of Systematic Reviews (registration number: CRD42023437904). It was compiled following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) principles and guidelines between July 2023 and June 2024. We searched PubMed, Scopus, ScienceDirect, Google Scholar, and governmental and non-governmental institutions to find published and gray literature relevant to the review objectives from 2005 to June 2024. Studies conducted in SSA, published in English, focusing on MSM aged ≥15 years and also reported condom and lubricant use were considered for this review. Following the removal of duplicates and ineligible articles, 40 studies out of 202 reviewed were selected for the study. The most common study designs were cross-sectional surveys (n = 32) followed by prospective cohorts (n = 4), integrated bio-behavioral surveillance surveys (n = 3), and intervention studies (n = 1). Of the 40 eligible studies included in this review, half (n = 20) reported consistent use of condoms but without lubricants, three reported consistent use of condoms with lubricants but did not specify the lubricant type, six reported consistent condom use with water-based condom-compatible lubricants, and 11 reported only condom use but not consistent usage. Factors linked to consistent condom use with lubricants among MSM from various studies included higher educational level, knowing one’s HIV status, accessibility challenges, and older age. Having a high level of self-worth and HIV risk-reduction counseling was also associated with a consistency of condom use amongst MSM who engaged in receptive anal sex. This review indicates that only a few studies reported consistent condom use with lubricants and water-based compatible lubricants.